Double, double toil and trouble: transforming growth factor beta (TGF-β) in HIV infection - Harrison-Gleason, Jakob; Yerlioglu, Kayla L.; Halle, Ariel W.; Hultquist, Judd F.; Martinelli, Elena (Frontiers in Immunology, 2026)
Despite effective suppression of viral replication by antiretroviral therapy (ART), chronic HIV infection remains characterized by persistent low-level inflammation and progressive tissue damage, contributing to premature aging and an array of comorbidities including cardiovascular disease, HIV-associated neurocognitive disorders, liver disease, and fibrosis of multiple organs. Increased levels of transforming growth factor beta (TGF-β), characteristic of chronic HIV infection even in the context of ART, appear to be a common thread explaining these disparate comorbidities. As a pleiotropic cytokine with both immunosuppressive and pro-fibrotic properties, TGF-β exerts complex and sometimes paradoxical effects on the HIV lifecycle and pathogenesis. This review explores the multifaceted roles of TGF-β in HIV infection, with particular focus on three critical areas: immunosuppression, tissue fibrosis, and the regulation of viral latency. We discuss recent advancements in understanding the often-paradoxical role of TGF-β on HIV replication and latency dynamics, and how its different effects contribute to multiple mechanisms underlying HIV persistence, from inhibited immune responses and enhanced viral latency to impaired immune reconstitution. A more comprehensive understanding of the mechanisms by which TGF-β contributes to HIV persistence may illuminate novel therapeutic strategies targeting TGF-β signaling pathways for improved HIV treatment and progression toward functional cure.